Upper Bound of the Generalized p Value for the Population Variances of Lognormal Distributions with Known Coefficients of Variation - Rada Somkhuean; Sa-aat Niwitpong; Suparat Niwitpong (Journal of Probability and Statistics)
This paper presents an upper bound for each of the generalized p values for testing the one population variance, the difference between two population variances, and the ratio of population variances for lognormal distribution when coefficients of variation are known. For each of the proposed generalized p values, we derive a closed form expression of the upper bound of the generalized p value. Numerical computations illustrate the theoretical results.